Analysis of risk factors and intervention measures for postoperative bleeding in patients with diabetes after proctologic surgery based on a logistic regression model - Yu, Qiuxiang; Li, Peiyao; Li, Dan; Wang, Lin; Yu, Guoshuang; Li, Rui (Frontiers in Medicine, 2025)
ObjectiveThe purpose of this study was to analyse the risk factors for bleeding after proctologic surgery, provide a reference for clinical management and improve postoperative recovery in patients.MethodsThis study retrospectively analyzed the clinical data of patients undergoing proctologic surgery in our hospital. Patients with postoperative bleeding comprised the study group, whereas those without bleeding formed the control group. A logistic regression model was used to analyse the risk factors for postoperative bleeding in patients undergoing proctologic surgery. A p-value < 0.05 was considered statistically significant.ResultsThe study found that the risk of postoperative bleeding in men was significantly higher than in women (p < 0.001). Hypertension was identified as an independent risk factor for bleeding (p < 0.001). The incidence of bleeding was significantly higher in patients who received preoperative antibiotics (p = 0.032). The proportion of patients with postoperative dry stool in the bleeding group was significantly higher than in the control group (p < 0.001). The under the curve (AUC) of the prediction model was 0.820, 95%CI: 0.760–0.880, the sensitivity was 72.4%, and the specificity was 82.7%.ConclusionThis study demonstrated that the risk of postoperative bleeding after proctologic surgery was closely associated with several factors, including male sex, hypertension, preoperative antibiotic use and postoperative constipation, all of which significantly increased the risk of bleeding.